FAKTOR YANG MEMPENGARUHI KEMAUAN MEMBAYAR PAJAK WAJIB PAJAK ORANG PRIBADI (Students' Journal of Accounting and Banking, 2013)
This research intent to know influential factors to willingness pay taxes. Case study on individual taxpayers who perform as a freelancer that registered at KPP Pratama Semarang Gayamsari. That factor are pay taxes awareness, knowledge and understanding of taxpayer, a good perception of the effectiveness of the taxation system, and attitude.The amount of samples used in this syudy of 80 respondent with convenience sampling which is sample determination tech bases even coincidence, found population member researcher and has the honour to become respondent at makes sample. The data used are the primary data and secondary data analysis used was a qualitative analysis and the coefficient of determination, and test hypotheses using t test and F test.Based on data analysis and hypothesis testing can be concluded variable pay taxes awareness, knowledge and understanding of taxpayer, a good perception of the effectiveness taxation system, and attitude has a significant and positive influence on purchase decision willingness pays taxes.Keywords: pay taxes awareness, knowledge and understanding, perception, attitude, and willingness to pay tax.